2020
DOI: 10.1051/0004-6361/201937245
|View full text |Cite
|
Sign up to set email alerts
|

White dwarf deflagrations for Type Iax supernovae: polarisation signatures from the explosion and companion interaction

Abstract: Growing evidence suggests that Type Iax supernovae might be the result of thermonuclear deflagrations of Chandrasekhar-mass white dwarfs in binary systems. We carry out Monte Carlo radiative transfer simulations and predict spectropolarimetric features originating from the supernova explosion and subsequent ejecta interaction with the companion star. Specifically, we calculate viewing-angle dependent flux and polarisation spectra for a 3D model simulating the deflagration of a Chandrasekhar-mass white dwarf an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…These models cover two explosion mechanisms: delayed detonation (ddt) and pure deflagration (def), and compare two setups for the central ignition: many ignition points (N100) or a few ignition points (N5). The properties of these models have been investigated in details for the SN phase (Sim et al 2013;Kromer et al 2013;Bulla et al 2016Bulla et al , 2020, we present here for the first time how they evolve into the SNR phase. We simulated the hydro evolution for 500 yr, in an ambient medium assumed to be uniform in order to separate concerns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These models cover two explosion mechanisms: delayed detonation (ddt) and pure deflagration (def), and compare two setups for the central ignition: many ignition points (N100) or a few ignition points (N5). The properties of these models have been investigated in details for the SN phase (Sim et al 2013;Kromer et al 2013;Bulla et al 2016Bulla et al , 2020, we present here for the first time how they evolve into the SNR phase. We simulated the hydro evolution for 500 yr, in an ambient medium assumed to be uniform in order to separate concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas all our ddt models fully unbind the WD, def models are often partial explosions that leave compact remnants behind, that is, a WD with an unusual composition -which may have been observed, see Vennes et al (2017). Such a weak explosion like N5def is thought to be a good model for SN2002cx-like SNe Ia (Kromer et al 2013; see also Jordan IV et al 2012 for a similar model) and maybe for the larger class of Type Iax SNe (Bulla et al 2020). N5def is an asymmetric explosion that leaves behind a ≈ 1 M WD remnant.…”
Section: Sn Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, it has been shown that weak deflagration explosion of a M Ch CO WD and/or a hybrid CONe WD can well reproduce the observational features of Iax events, SN 2005hk (a proto-typical SN Iax) and SN 2008ha (the faint Iax event), respectively (Kromer et al 2013(Kromer et al , 2015. Bulla et al (2020) also suggested that the maximum-light polarization signal seen in SN 2005hk can be well interpreted by asymmetries caused by SN explosion itself and by the ejectacompanion interaction in the weak deflagration explosion model. Therefore, the weak deflagration explosion of a M Ch WD seems to be a potential model for SNe Iax (but see also Hoeflich et al 1995;Stritzinger et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the progenitors and explosion mechanism of SNe Iax remain a mystery, it has been suggested that incomplete pure deflagration explosions of near-Chandrasekhar-mass WDs within the SD scenario are able to reproduce the characteristic observational features of SNe Iax (e.g. Jordan et al 2012;Kromer et al 2013Kromer et al , 2015Fink et al 2014;Liu et al 2015b;Bulla et al 2020). Recently, using the smoothed-particle hydrodynamics (SPH) code S G (Springel et al 2001;Pakmor et al 2012a), Liu et al (2013c) have performed 3D hydrodynamical simulations of SN ejecta-companion interaction by assuming that SNe Iax are generally generated from pure deflagration explosions of near-Chandrasekhar-mass WDs in WD + MS progenitor systems.…”
Section: Introductionmentioning
confidence: 99%